Analysis of temperature and concentration polarizations for performance improvement in direct contact membrane distillation. (December 2019) - Kuang, Zhengfei; Long, Rui; Liu, Zhichun; Liu, Wei
Highlights: Flowrate and concentration variation along the flow direction is considered. Baffles promote the TP and restrain the CP. Baffles significantly enhance the transmembrane partial vapor pressure difference. With semi-circle shaped baffle employed, the water production is increased by 28.3%. Abstract: Regarding numerical simulation of the direct contact membrane distillation (DCMD) based on computational fluid dynamics, the variation of mass flowrate and concentration along the flow direction has merely been considered. To relieve such issues, a refined model coupling Navier-Stokes equations and species transportation equations is employed to illustrate the flow, heat and mass transfer characteristics in the flat sheet DCMD process. The potential of attaching baffles to the feed/permeate channel shell to improve the DCMD performance has been investigated under the laminar and turbulent flow, respectively. Modified channels were designed to have regularly distanced baffles with various shapes at different characteristic lengths. The heat transfer coefficient, mass transfer coefficient, temperature polarization coefficient, concentration polarization coefficient, mass flux, thermal efficiency and power consumption of the original and modified modules are calculated and compared. Results reveal that a structural modification could promote the temperature polarization phenomenon and restrain the concentration polarization phenomenon, thus to improve the module water production. However, the presence of baffles contributes to extra power consumption. At a feed flow Reynolds number of 358, for module with semi-circle shaped baffle at the characteristic length of 1 mm, the water production is increased by 28.3%, meanwhile the hydraulic energy consumption is increased by 3.32-fold. Under the laminar flow, the water production can be significantly improved by attaching baffles in the channel shells, which is not appealing under the turbulent flow due to the huge augment in hydrodynamic loss.